Bunga rampai pemikiran Islam / Muhammad Ismail ; penerjemah, Nurkhalis ; penyunting, A.R. Nasser A. Saefullah - ISMAIL, Muhammad; Nurkhalis; Saefullah, A; Nasser, AR (Gema Insani Press, 1995)
198 hlm. ; 18 cm.